Ravel: In Search of Lost Dance - Premiere recording of Ravel's Piano Trio on historical instruments - Boondiskulchok, Prach (Berlin, Germany Deutsche Grammophon, 2023)
Instruments used:Erard 1882;Strings with open-wound gut and late 19th set up.
The Linos Piano Trio presents the music of Ravel in a fascinating light, performing on period instruments and exploring Ravel’s own relationship with the past.As well as the Piano Trio in A minor, the disc includes Linos’s own arrangements of Ravel’s Pavane pour une infante défunte and Le Tombeau de Couperin — an extension of their ‘Stolen Music’ project, in which they collaboratively re-imagine orchestral masterpieces as if they had been initially conceived for Piano Trio.By using period instruments, the Linos players find a wider range of colour in Ravel’s music, and a more timbrally-entwined balance between the three instruments. Violinist Konrad Elias-Trostmann and cellist Vladimir Waltham play on a combination of plain and wound gut strings, while Pianist Prach Boondiskulchok performs on an 1882 Érard Concert Grand piano, the same make and a very similar model to the piano Ravel himself owned and composed with.While the Pavane, composed in 1899, depicts an imagined dance in a 17th-century Spanish court and the Tombeau presents a series of neo-baroque dances, composed against the backdrop of the First World War, the Linos players have also come to see the Piano Trio as a set of dances. Completed in 1914, immediately before Ravel enlisted for military service, the Trio speaks to Le Tombeau across the historical divide of the outbreak of war in their ‘search for lost dances’: “the Piano Trio imagines dances of his childhood, dances of faraway places, dances of victory and death, while Le Tombeau reimagines dances from faraway times”.
FRIS
Editorial review
Keywords: Declassifying the Classics: Rhetoric, Technology, and Performance, 1750-1850